2002
DOI: 10.2355/isijinternational.42.450
|View full text |Cite
|
Sign up to set email alerts
|

Retained Austenite Characteristics and Stretch-flangeability of High-strength Low-alloy TRIP Type Bainitic Sheet Steels.

Abstract: Retained austenite characteristics and stretch-flangeability in low alloy TRIP type bainitic sheet steels with different silicon and manganese contents were investigated for automotive applications. As increasing silicon and manganese contents, an initial volume fraction of retained austenite film along bainitic ferrite lath boundary was increased in accompany with a decrease in the carbon concentration. An excellent stretchflangeability was completed in the steels containing a small amount of stable retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 12 publications
3
78
1
2
Order By: Relevance
“…These results are the same as previous studies. 18,19) Figure 3 shows the relationship between total charged hydrogen concentration (H T ) and tensile strength (TS ) of TBF steels after hydrogen-charging for 15 min. The total charged hydrogen concentration is hardly changed by aluminum addition.…”
Section: Microstructure and Tensile Propertiesmentioning
confidence: 99%
“…These results are the same as previous studies. 18,19) Figure 3 shows the relationship between total charged hydrogen concentration (H T ) and tensile strength (TS ) of TBF steels after hydrogen-charging for 15 min. The total charged hydrogen concentration is hardly changed by aluminum addition.…”
Section: Microstructure and Tensile Propertiesmentioning
confidence: 99%
“…Their interests are manifold since they combine promising tensile behavior with improved in-use properties, as reported by previous researches. [4][5][6][7][8][9][10][11][12] Their mechanical behavior is strongly impacted by the characteristics of their microstructures. Indeed, the bainitic transformation is one of the most complex phase transformations in steels and can lead to various microstructures exhibiting different mechanical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In general, Si suppresses carbide formation in steel, 5,15) similarly to Al. 9) Thus, it is considered that Si addition of 1.5 mass% results in such microstructural characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…According to De Cooman, 1) first-generation advanced high-strength steels (AHSSs), such as dual-phase steel, TransformationInduced Plasticity-aided steel (TRIP-aided steel) with a polygonal ferrite matrix, and so on, have contributed considerably to the weight reduction and crash safety of recent automobiles because of their good combination of formability and tensile strength. Although second-generation AHSSs such as Twinning-Induced Plasticity steel (TWIP steel) 2) have not been applied so widely to automotive parts, thirdgeneration advanced AHSSs such as TRIP-aided bainitic ferrite steel (TBF steel) [3][4][5][6][7][8][9] and quenching and partitioning steel (Q&P steel), 10) with good formability (stretch-flangeability and bendability) and ultra-high strength (980-1 470 MPa) are expected for future automotive applications. For the achievement of a tensile strength of more than 2.0 GPa, quenching-partitioning-tempering (Q-P-T) steel with a martensite matrix was developed by Wang et al 11) They reported that ultra-high-strength TRIP-aided steel can be developed through the utilization of the martensite structure.…”
Section: Introductionmentioning
confidence: 99%